# Solve the linear equations by considering y as a function of x, that is, \displaystyle{y}={y}{\left({x}\right)}.{x}{y}'+{\left({1}+{x}\right)}{y}={e}^{{-{x}}} \sin{{2}}{x}

Solve the linear equations by considering y as a function of x, that is, $$\displaystyle{y}={y}{\left({x}\right)}.{x}{y}'+{\left({1}+{x}\right)}{y}={e}^{{-{x}}} \sin{{2}}{x}$$

• Questions are typically answered in as fast as 30 minutes

### Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

Elberte

Variation of parameters
First, solve the linear homogeneous equation by separating variables.
Rearranging terms in the equation gives
$$\displaystyle{x}{y}'=-{\left({1}+{x}\right)}{y}\Leftrightarrow\frac{{\left.{d}{y}\right.}}{{\left.{d}{x}\right.}}=-\frac{{{\left({1}+{x}\right)}{y}}}{{x}}\Leftrightarrow\frac{d}{{y}}=-\frac{{{\left({1}+{x}\right)}{\left.{d}{x}\right.}}}{{x}}$$
Now, the variables are separated, x appears only on the right side, and y only on the left.
Integrate the left side in relation to y, and the right side in relation to x
$$\displaystyle{x}{y}'=-{\left({1}+{x}\right)}{y}\Leftrightarrow\frac{{\left.{d}{y}\right.}}{{\left.{d}{x}\right.}}=-\frac{{{\left({1}+{x}\right)}{y}}}{{x}}\Leftrightarrow\frac{d}{{y}}=-\frac{{{\left({1}+{x}\right)}{\left.{d}{x}\right.}}}{{x}}$$
Let’s solve the integral on the right side.
$$\displaystyle\int\frac{{{\left({1}+{x}\right)}{\left.{d}{x}\right.}}}{{x}}=\int{\left(\frac{1}{{x}}+\frac{x}{{x}}\right)}{\left.{d}{x}\right.}$$
$$\displaystyle=\int{\left(\frac{1}{{x}}+{1}\right)}{\left.{d}{x}\right.}$$
$$\displaystyle=\int\frac{{\left.{d}{x}\right.}}{{x}}+\int{\left.{d}{x}\right.}$$
$$\displaystyle={\ln}{\left|{x}\right|}+{x}+{c}$$
Therefore,
$$\displaystyle{\ln}{\left|{y}\right|}=-{\ln}{\left|{x}\right|}-{x}+{c}$$
By taking exponents, we obtain
$$\displaystyle{\left|{y}\right|}={e}^{{-{\ln}{\left|{x}\right|}-{x}+{c}}}=\frac{1}{{{\left|{x}\right|}{e}^{x}}}\cdot{e}\cdot{c}$$
Hence,we obtain
$$\displaystyle{y}=\frac{C}{{{x}{e}^{x}}}$$
where $$\displaystyle{C}\:=\pm{e}^{c}{\quad\text{and}\quad}{y}_{{c}}=\frac{1}{{{x}{e}^{x}}}$$ is the complementary solution.
Next, we need to find the particular solution $$\displaystyle{y}_{{p}}$$.
Therefore, we consider $$\displaystyle{u}{y}_{{c}}$$, and try to find u, a function of x, that will make this work.
Let’s assume that $$\displaystyle{u}{y}_{{c}}$$, is a solution of the given equation. Hence, it satisfies the given equation.
Write the equation in the standard form (divide it by x 4 0)
$$\displaystyle{y}'+\frac{{{\left({1}+{x}\right)}{y}}}{{x}}=\frac{{{e}^{{-{x}}} \sin{{2}}{x}}}{{x}}$$
Substituting $$\displaystyle{d}{i}{s}{p}{l}{a}{y}{s}{t}{y}\le{\left\lbrace{u}\right\rbrace}{\left\lbrace{y}\right\rbrace}_{{{\left\lbrace{c}\right\rbrace}}}$$ and its derivative in the equation gives
$$\displaystyle{u}{y}_{{c}}$$
$$\displaystyle{\left({u}{y}_{{c}}\right)}'+\frac{{{\left({1}+{x}\right)}{u}{y}_{{c}}}}{{x}}=\frac{{{e}^{{-{x}}} \sin{{2}}{x}}}{{x}}$$
$$\displaystyle{u}'{y}_{{c}}+{u}{\left({y}'{c}+\underbrace{{\frac{{{\left({1}+{x}\right)}{y}_{{c}}}}{{x}}}}\right)}{{={0}\ \text{since}\ {y}_{{c}}\text{is a solution}}}$$
Therefore,
$$\displaystyle{u}'{y}_{{c}}=\frac{{{e}^{{-{x}}} \sin{{2}}{x}}}{{x}}\Rightarrow{u}'=\frac{{\frac{{{e}^{{-{x}}} \sin{{2}}{x}}}{{x}}}}{{y}_{{c}}}$$
which gives
$$\displaystyle{u}=\int\frac{{\frac{{{e}^{{-{x}}} \sin{{2}}{x}}}{{x}}}}{{{y}_{{c}}}}{\left.{d}{x}\right.}$$
Now, we can find the function u :
$$\displaystyle=\int\frac{{{{x}}{{e}}^{x}\cdot{e}^{{-{x}}} \sin{{2}}{x}}}{{{{x}}}}{\left.{d}{x}\right.}$$
$$\displaystyle=\int \sin{{2}}{x}{\left.{d}{x}\right.}$$
$$\displaystyle=-\frac{1}{{2}} \cos{{2}}{x}+{e}$$
Since we need to find only one function that will make this work, we don’t need to introduce the constant of integration c. Hence,
$$\displaystyle{u}=-\frac{1}{{2}} \cos{{2}}{x}$$
Recall that $$\displaystyle{y}_{{p}}={u}{y}_{{c}}$$. Therefore,
$$\displaystyle{y}_{{p}}-\frac{1}{{2}}\cdot\frac{{ \cos{{2}}{x}}}{{{x}{e}^{x}}}$$
The general solution is
$$\displaystyle{y}={C}{y}_{{c}}+{y}_{{p}}$$
$$\displaystyle=\frac{C}{{{x}{e}^{x}}}-\frac{1}{{2}}\cdot\frac{{ \cos{{2}}{x}}}{{{x}{e}^{x}}}$$
$$\displaystyle=\frac{{{C}-\frac{1}{{2}}\cdot \cos{{2}}{x}}}{{{x}{e}^{x}}}$$
Integrating Factor technique
First, write the equation in the standard form (divide it by $$\displaystyle{x}\ne{0}$$)
$$\displaystyle{y}'+\frac{{{\left({1}+{x}\right)}{y}}}{{x}}=\frac{{{e}^{{-{x}}} \sin{{2}}{x}}}{{x}}$$
This equation is linear with $$\displaystyle{P}{\left({x}\right)}=\frac{{{1}+{x}}}{{x}}{\quad\text{and}\quad}{Q}{\left({x}\right)}=\frac{{{e}^{{-{x}}} \sin{{2}}{x}}}{{x}}$$
, Hence,
$$\displaystyle{h}=\int{P}{\left.{d}{x}\right.}\int\frac{{{1}+{x}}}{{x}}{\left.{d}{x}\right.}={\ln}{\left|{x}\right|}+{x}$$
So, an integrating factor is
$$\displaystyle{e}^{h}={e}^{{{\ln}{\left|{x}\right|}+{x}}}={x}{e}^{x}$$
and the general solution is
$$\displaystyle{y}{\left({x}\right)}={e}^{{-{h}}}{\left({c}+\int{Q}{e}^{h}{\left.{d}{x}\right.}\right)}$$
$$\displaystyle=\frac{1}{{{x}{e}^{x}}}{\left({c}+\int\frac{{{1}+{x}}}{{l{{x}}}}{{x}}{e}^{x}\right)}$$
$$\displaystyle=\frac{1}{{{x}{e}^{x}}}{\left({c}+\int\frac{{{{e}}^{{-{x}}} \sin{{2}}{x}}}{{{{x}}}}\cdot l{{x}}{{e}}^{x}\right)}$$
$$\displaystyle=\frac{{{c}-\frac{1}{{2}}\cdot \cos{{2}}{x}}}{{x}}{e}^{x}$$